A Structural Equation Modeling On Financial Health For Businesses - Sudhin, Mrs. Serah; Shamrao P., Dr. Ghodake; Saxena, Dr. Pooja Swaroop; Saikia, r. Bhabajyoti; Rai, Dr. Manish D; Singh, Prof. Sanjay Kumar (Migration Letters, 2024)
The SEM refers to the structural equation model and is used as the tool for analyzing the statistical data. With the help of this tool, different variables are identified and along with this, the relationships between the variables are also identified. The assumption of the correlation between the variables is dejected by the SEM. Moreover, SEM is also capable of performing investigations by using 200 to 400 sample sizes. Only by proceeding with a single analysis step the construction of the relationship between the two different variables is performed which makes the SEM method widely selected. Along with this the models used in the equation process for measuring stand for the theories.